English language - Ahdar, Ahdar; Musyarif, Musyarif; Ramlia, Nurleli; Hikma, Nurul; Munalestari, Evi (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine the effectiveness of using comic media in increasing students’ motivation in social science subjects. This study is an experimental study with a draft factorial pre-test post test involving variable use of comic media. This study was conducted at State Madrasah Tsanawiyah (MTsN) of Parepare city which involved two study groups in class VIII with a total of 24 students as respondents. The instrument of comic media use was declared valid and reliable with a Cronbach Alpha value of 0.917 containing 24 statement items. Descriptive analysis of comic media use obtained a mean pre-test value of 46.73 and post-test 82.80 which means that the results showed an increase motivation to learn after being given a learning treatment using comic media. The hypothesis test shows a significance value of 0.0001 which means the use of learning comic media provides better results than the use of learning media in the form of Power points. This happens because comic media is interesting, entertaining, and easy for learners to understand. Abstrak: Penelitian ini bertujuan untuk mengetahui efektivitas penggunaan media komik pada mata pelajaran IPS. Penelitian ini adalah penelitian eksperimen dengan rancangan faktorial pre test-post test yang melibatkan variabel penggunaan media komik. Penelitian ini dilaksanakan di MTs Negeri Kota Parepare yang melibatkan dua rombongan belajar di kelas VIII dengan total 24 siswa sebagai responden dalam penelitian. Instrumen efektivitas penggunaan media komik dinyatakan valid dan reliabel dengan nilai Cronbach Alpha 0.917 yang berisi 24 item pernyataan. Hasil analisis Deskriptif penggunaan media komik diperoleh nilai mean Pre Test 46,73 dan Post Test 82,80 artinya hasil menunjukkan adanya peningkatan setelah diberikan treatmen pembelajaran menggunakan media komik. Uji hipotesis menunjukkan nilai signifikan sebesar 0.0001 yang berarti penggunaan media komik pembelajaran memberikan hasil yang lebih baik dibandingka dengan penggunaan media pembelajaran berbentuk Power point. Hal ini terjadi karena media komik menarik, menghibur, dan mudah untuk dipahami oleh peserta didik.